Strategy for Strengthening Elementary School Literacy - Sindi Natasya Baco; Sri Nindi Midu; Yulfin Ismail (Global Scientific Publishing, 2023)
Literacy is read printed words , speak clearly and acquisition through various literacy activities. The aim of this research was to strengthen literacy in children. The type of method applied in this research is Classroom Action Research (PTK). The research was carried out at the first meeting, as many as 15 students were present, complete and no one was absent. Before the implementation of cycle I, data was obtained from 11 out of 15 students or 75% of students who had not yet demonstrated good motivation and literacy behavior, and as many as 25% of students had demonstrated good motivation and literacy behavior.
Keywords: Literacy; Strengthening; Literacy Strengthening Strategy